The impact of COVID-19 on resident doctors as the frontline in health services - Maghfirah, Desi; Yusuf, Muhammad; Pamungkas, Subhan Rio; Firdausa, Sarah; Eljatin, Muhammad Ridho Akbar; Febriyanti, Sherina Arfi (Intelektual Pustaka Media Utama, 2024)
As the number of confirmed cases of COVID-19 increases, the workload due to the pandemic can affect health workers and increase the risk of psychological stress. Psychological factors such as anxiety can cause various physiological responses, including gastroesophageal reflux disease (GERD) symptoms. The persistent symptoms of GERD can reduce the patient's quality of life. A cross-sectional survey was conducted in October 2021 at the Dr. Zainoel Abidin Regional General Hospital, Banda Aceh. A total of 91 Specialist Medical Education Program responded to the study. Data from respondents were collected through the generalized anxiety disorder-7 (GAD-7), GERD-Q, and WHOQOL-BREF questionnaires. The statistical analysis used was the contingency coefficient test. The results showed that 9.9% of respondents experienced suggestive GERD, minimal anxiety (92%), and good quality of life (51.6%). There was a significant relationship between anxiety levels and quality of life and the GERD prevalence of Specialist Doctor Education Program Participants during the COVID-19 pandemic (p<0.05). Most Specialist Medical Education Program participants did not suffer from GERD with minimal anxiety, followed by mild and moderate anxiety. The majority had a good and moderate quality of life during the COVID-19 pandemic.